A influência do pediatra e suas intervenções no sucesso do aleitamento materno exclusivo em pacientes submetidos à cesariana eletiva - Silveira, Carolina Menna Barreto (2016)
Recent data from scientific literature show low exclusive breastfeeding (EBF) rates in the world, and diversity in the factors that influence it. However, the number of studies about the power of pediatricians and their interventions on duration of EBF is still limited. Objective: To determine the influence of the pediatrician and their interventions on the success of EBF at 3 and 6 months of age in full-term newborns (FNT), undergoing elective cesarean delivery. Methods: A cohort study in a private hospital in Brazil. Questionnaires to mothers at discharge, at 7 days, 3 and 6 months of life were applied. At the day of discharge, the contact was in person, while the following steps was by phone calling. To evaluate the association between categorical variables, chi-squared tests or Fisher's exact were used. Results: The final sample consisted of 907 mother-baby pairs, assisted by 32 pediatricians. The influence of the pediatrician was significant in EBF at 3 months of age (p=0.001). The prevalence of complement in the first prescription varied significantly among pediatricians (31.6% to 100%, p <0.001) and was negatively associated with the EBF at 3 months (p=0.003). When comparing the prevalence of the use of bottles and pacifiers at the first 7 days of life, among the pediatricians, there was a significant difference (p=0.005). The use of pacifiers at 7 days and 3 months was negatively associated with the EBF at 3 months (p<0.001). FNTs who used a bottle at 7 days showed lower prevalence of EBF until sixth month of life. Conclusion: This study provides evidences about the influence of the pediatrician in the prevalence and duration of exclusive breastfeeding at third month of life. This reinforces the need to improve their knowledge, attitudes and practices on breastfeeding.